Addressing barriers to improve biocrust colonization and establishment in dryland restoration. (5th November 2019) - Antoninka, Anita; Bowker, Matthew A.; Barger, Nichole N.; Belnap, Jayne; Giraldo‐Silva, Ana; Reed, Sasha C.; Garcia‐Pichel, Ferran; Duniway, Michael C.
Abstract : Methods to reduce soil loss and associated loss of ecosystem functions due to land degradation are of particular importance in dryland ecosystems. Biocrusts are communities of cyanobacteria, lichens, and bryophytes that are vulnerable to soil disturbance, but provide vital ecosystem functions when present. Biocrusts stabilize soil, improve hydrologic function, and increase nutrient and carbon inputs. Methods to reestablish biocrust rapidly, when lost from ecosystems, have the potential to restore important dryland ecosystem functions and thereby increase probability of successful rehabilitation. The aim of this study was to identify habitat ameliorations to enhance the success of biocrust inoculation by: (1) reducing physiological stress on biocrusts and increasing resource availability (using shade, soil surface roughening, and watering), and (2) stabilizing mobile soils (using straw borders, three soil tackifiers [soil stabilizers], and a combination of shade, water, roughening, and tackifier). In the Great Basin Desert on the Utah Test and Training Range near Salt Lake City, we applied field‐harvested biocrust material to experimental plots on coarse‐ and fine‐textured soils with the top 2 cm of soil and biocrust removed. Habitat ameliorations were applied with and without biocrust addition. Shade provision increased biocrust cover 50% over controls. Biocrust cover and soil stability were 65% lower in straw border plots relative to controls. Soil tackifiers, alone and in combination with resource augmentation and stress reduction, did not improve cover and stabilization over inoculated controls. We found variability in recovery by time and between soil types. These results suggest plausible strategies to improve success of biocrust inoculation.